Variants in economic theory : selected works of Hal R. Varian - Varian, Hal R. (Cheltenham, UK Northampton, MA : Edward Elgar Pub., 2000)
This book contains papers on economic growth and technical change,monetary and value theory, the theory of second best,international trade theory, political economy and methodology.
A collection of 21 articles and book chapters, with some corrections, previously published between 1967-1995, plus a "biographical reflections" chapter written by Varian.
Includes bibliographical references and index.
aia 16/09/13
Loan
Keywords: Varian, Hal R; Microeconomics; Finance; Econometrics; Economists -- United States